Regional differences in residential demand for very high bandwidth broadband internet in 2025 - Sonia Strube Martins; Christian Wernick (International Telecommunications Society (ITS), 2019)
WIK has developed a 'market potential' model in order to assess how bandwidth requirements may evolve in the near future (i.e. to 2025). Originally developed in 2011, this model was revised and updated in 2017 to reflect emerging applications and new developments. Originally developed for the forecast of bandwidth demand in Germany, it has been applied to estimate bandwidth demand in the UK and Flanders in Belgium, too. The comparison of the results of the demand forecast in different regions allows to identify how usage patterns and demographic structures impact bandwidth demand. This information can be used to develop measures which trigger broadband demand and digitisation. This paper focuses on the results of bandwidth demand forecasts in Germany, the UK and Flanders and the impact the difference between user profiles and household structure has on the forecast of bandwidth demand. Furthermore, we update the input data of the market potential model to reflect recent developments and new research. Our paper is structured as follows: We start with a short introduction on broadband availability and demand in Germany, UK and Flanders in Chapter 2. The methodology of the WIK market potential model is explained in chapter 3 followed by the allocation of applications to user types and the household structure in the different regions. The forecasts of bandwidth demand in Germany, the UK and Flanders in Belgium and conclusions are presented in chapter 4.
Keywords: 330